CHARACTERIZATION OF DIFFERENT OVARIAN MASSES USING IOTA ULTRASOUND RULES: A CROSS-SECTIONAL STUDY. - Singh, Sumity; Kumari, Manisha; Suman, Sanjay Kumar; Bharti, Shweta (Student’s Journal of Health Research Africa, 2024)
Background An adnexal lump in a woman is a common clinical condition. Accurately defining ovarian cancers is essential because it facilitates the identification of benign ovarian masses, which can then be treated conservatively to lower morbidity. Aim The purpose of the investigation was to determine the diagnostic value of IOTA ultrasonography rules, as well as to assess and evaluate the guidelines’ sensitivity and specificity about histological diagnosis and their suitability for use as a tool at our tertiary care center for the early detection of ovarian cancer. Methods A cross-sectional investigation was carried out including women who had been recruited with at least one adnexal mass. When two adnexal masses were present, the analysis took into account the mass with the more intricate ultrasonography morphology. The masses were characterized by evaluating the sonographic morphology of the masses and doing a color Doppler examination. A link between sonography and histopathology was found using suitable statistical techniques. Results Using these guidelines, 50 individuals underwent USG; of these, 31 had benign, 15 had cancer, and 4 had unclear results. 30 of the 31 masses on the final HPE report that the simple rules had predicted to be benign turned out to be benign based on histology. Histology revealed that 14 of the 15 masses that the basic rules predicted to be cancer were malignant. Conclusion The study evaluates the effectiveness of simple rules in distinguishing between benign and malignant adnexal masses. Despite yielding inconclusive results in about 6.4% of cases, the diagnostic performance improves with extensive training provided to resident doctors. Recommendations It is recommended to integrate the IOTA ultrasonography rules into tertiary care gynecological diagnostic protocols. Comprehensive training for resident doctors is crucial to enhance diagnostic accuracy and minimize inconclusive results.